Sistema de inferencia de lógica difusa para la evaluación del riesgo de transformadores de distribución del alimentador Pío Jaramillo de la ciudad de Loja. - Gutiérrez Celi, Juan Pablo (2022)
This research uses the fuzzy logic inference methodology to determine the risk index of the Pío Jaramillo feeder line distribution transformers in the city of Loja. For this study, the variables that have more impact on the useful life of the transformers are analyzed, such as the current loadability, age of the units, and the capacity of each transformer. Using the Fuzzy Logic ToolBox of MatLab software, the different results are analyzed according to the rules established for each case. Likewise, the membership functions for each input and output variable are established. Finally, the results are compared in each transformer to find the relationship between the selected variables and the risk index in each unit. Keywords: Fuzzy, Matlab, transformer, risk index, health index, consequence factor.